Fulfillment of Political Rights of Persons with Disabilities in the 2024 Elections in Indonesia - Eliyanti, Roulita; Sinaga, Budiman (Golden Ratio of Data in Summary, 2025)
In a democratic system, regional head elections (Pilkada) are one of the important pillars to elect leaders and representatives of the people. However, inaccurate voter data in the integrity of elections often causes problems in the implementation of elections including double data. Double data not only undermines the principle of fairness but also has the potential to reduce public trust in democracy. Therefore, election monitoring is essential to maintain the fairness and openness of the voting process. People's constitutional rights are affected by this issue, as they need assistance to report changes in voter data or match unregistered data. Almost all communities in Medan have conducted matching and research (coklit) properly, according to the election monitoring results. However, the issue of double data is still a problem that must be monitored again by Bawaslu. The author collects information about the 2024 Pilkada from the Election Supervisory Board of Medan City. That there are still many double data that occur in the community. The purpose of this research is to find out how well the coklit works to avoid double data and how it affects voting and fairness. This research shows that most citizens of Medan City have followed the procedures when conducting coklit, thus reducing the possibility of double data. Transparency, public trust, and community engagement in the elections also increased as a result. In addition, this monitoring activity also provides suggestions for improving the double data prevention system, including increasing cooperation between election organizers and independent monitors, expanding coklit socialization to the community, and using artificial intelligence-based technology for automatic detection. Such measures are essential to ensure integrity, fairness and transparency in elections.